2010
DOI: 10.1016/j.steroids.2009.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aromatase, androgen and estrogen receptors in peripheral target tissues in diabetes

Abstract: Our previous studies have shown that diabetes in the male streptozotocin (STZ)-induced diabetic rat is characterized by a decrease in circulating testosterone and concomitant increase in estradiol levels. Interestingly, this increase in estradiol levels persists even after castration, suggesting extra-testicular origins of estradiol in diabetes. The aim of the present study was to examine whether other target organs of diabetes may be sources of estradiol. The study was performed in male Sprague-Dawley non-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
8
26
0
Order By: Relevance
“…Salyer et al [37], showed expression of P450aro also in embryonic rat RPE, and a recent study reports aromatase also in the capillary of choroid of rats [54]. Our studies have proved E2 synthesis from aromatization of testosterone in a neurosteroidogenic pathway, via cholesterol, progesterone and/or testosterone metabolism [2,3,5].…”
Section: Enzymes and Synthesissupporting
confidence: 68%
See 2 more Smart Citations
“…Salyer et al [37], showed expression of P450aro also in embryonic rat RPE, and a recent study reports aromatase also in the capillary of choroid of rats [54]. Our studies have proved E2 synthesis from aromatization of testosterone in a neurosteroidogenic pathway, via cholesterol, progesterone and/or testosterone metabolism [2,3,5].…”
Section: Enzymes and Synthesissupporting
confidence: 68%
“…In diabetes, E2 effects appear indeed to mediate opposite effects upon the tissue affected [54]. For instance, the elevated expression of aromatase and ERα in the kidney of men may contribute to the development and progression of renal disease, but the same elevation of the oestrogenic parameters in the retina and choroid capillaries may prevent retinopathy [54]. Neuroactive steroid levels (pregnenolone, progesterone and its metabolites, testosterone and its metabolites, and dehydroepiandrosterone) are decreased in several central and peripheral regions of the nervous system of diabetic rats, mostly in accordance with sex-and regional-specificity [141].…”
Section: Oestrogen Retinal Neuroprotectionmentioning
confidence: 98%
See 1 more Smart Citation
“…ARs are highly expressed in proximal tubule cells (8), cortical collecting ducts (4), afferent arterioles, glomerular endothelial cells, and podocytes (36). In target tissue, testosterone directly binds to the nuclear AR or converts to dihydrotestosterone, which binds the AR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rocha et al found the mRNA for 5 reductase, which translates the enzyme which converts testosterone to the more active DHT in the RPE . Prabhu et al found AR protein in all layers of rat retina except the ganglion and outer nuclear layers (Prabhu et al 2010). However, in an interesting comparison of transformed rat cell lines from brain capillary endothelial cells and retinal capillary endothelial cells, Ohtsuki et al found dominant expression of AR in the brain capillary cells, but not the retinal capillary cells.…”
Section: Pericytesmentioning
confidence: 99%